The external wealth of Arab nations: Structure, trends, and policy implications. (24th November 2020) - Mohieldin, Mahmoud; Rostom, Ahmed; Zaki, Chahir
Abstract: The paper makes two contributions. First, it analyzes net foreign assets (NFA) and liabilities in selected Arab countries. Second, the paper examines the effects of policy variables that affect the accumulation of NFA and its components, analyzing how the existence of a sovereign wealth fund (SWF), the country's exchange rate regime, and the development of its financial system affect its NFA. The main findings show that the presence of a SWF is positively and significantly associated with foreign direct investment in Arab countries. While financial development matters, intermediate exchange rate regimes are associated to more uncertainty compared to fixed or flexible ones. Our results remain robust even we control for the endogeneity between SWF and NFA components.